168k views
2 votes
Simplily.
(x2-3x + 1) - (x + 2x + 7)

User Mind
by
5.5k points

1 Answer

5 votes

Answer:

The answer would be x^2 - 6x - 6.

Explanation:

Let's simplify this equation step-by-step.

First, distribute the negative sign:

= x2 − 3x + 1 + − 1 (x + 2x + 7)

= x2 + − 3x + 1 + − 1x + − 1 (2x) + (− 1) (7)

= x2 + − 3x + 1 + − x + − 2x + − 7

Next, combine like terms:

= x2 + − 3x + 1 + − x + − 2x + − 7

= (x2) + (− 3x + − x + − 2x) + (1 + − 7)

= x2 + − 6x + − 6

Therefor, your answer would be x2 − 6x − 6

Hope this helps!

User Michael Defort
by
5.6k points